Analisis Gambar “Kesetaraan Gender” Dalam Dunia Digital: Sebuah Eksplorasi Pada Ikatan Akuntan Indonesia - M. Ridho Hidayat; Sany Dwita (Universitas Negeri Padang, 2020)
The purpose of this study is to analyse how website of Institute of Indonesia Chartered Accountants contribute in gender equality of accounting profession in Indonesia. The processes of constructing and redesigning website and the selection of the images that appearing on it are analysed as important mechanism which not only reflect ‘realities’, but also contribute to proliferation diachronically existed power relations, gender inequalities, and gendered hierarchies. This study finds a proliferation of images of (accounting) women on structure of the profession even if men are still dominant. The outcome of this to encourage women participation in accounting profession. The empirical proof presented in this study, points toward a lack of images representing professional accounting women. But when women are represented, they are depicted in similar roles as like men roles. These findings explain that Institute of Indonesia Chartered Accountants has become progressive and attempted to reduce the exercises of gender inequality in the accounting profession and contribute to empower gender equality. This study argues that a proliferation in the representation of (accounting) women in Indonesia digital space would flourish a positive step towards the inclusion of women in the Indonesia profession.